Protection Of Patients’ Rights In The Event Of Electronic System Failures Leading To Delays In Service At Community Health Centres - Lisnaria Febriana Saragih; Redyanto Sidi; Muhamad Arif Sahlepi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Health service activities at Community Health Centers (Puskesmas) are increasingly dependent on electronic systems, so system failures can cause service delays and potentially violate patients’ rights. This condition requires legal protection and clear accountability of health service providers. This study aims to analyze electronic system failures at Puskesmas, their impact on services, the forms of legal protection available to patients, and the legal liability that may be applied. The research uses a normative juridical method based on the Health Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law. The results show that system failures lead to service delays and access barriers, with providers’ liability potentially taking administrative, civil, or criminal forms. This study emphasizes the importance of strengthening digital infrastructure and technical regulations to ensure the reliability of electronic health services at Puskesmas.